Arabidopsis MADS-box factor AGL16 is a negative regulator of plant response to salt stress by downregulating salt-responsive genes - Zhao, Ping-Xia; Zhang, Jing; Chen, Si-Yan; Wu, Jie; Xia, Jing-Qiu; Sun, Liang-Qi; Ma, Shi-Song; Xiang, Cheng-Bin (The New phytologist, 2021)
• Sessile plants constantly experience environmental stresses in nature. They must have evolved effective mechanisms to balance growth with stress response. Here we report the MADS-box transcription factor AGL16 acting as a negative regulator in stress response in Arabidopsis. • Loss-of-AGL16 confers resistance to salt stress in seed germination, root elongation and soil-grown plants, while elevated AGL16 expression confers the opposite phenotypes compared with wild-type. However, the sensitivity to abscisic acid (ABA) in seed germination is inversely correlated with AGL16 expression levels. • Transcriptomic comparison revealed that the improved salt resistance of agl16 mutants was largely attributed to enhanced expression of stress-responsive transcriptional factors and the genes involved in ABA signalling and ion homeostasis. We further demonstrated that AGL16 directly binds to the CArG motifs in the promoter of HKT1;1, HsfA6a and MYB102 and represses their expression. Genetic analyses with double mutants also support that HsfA6a and MYB102 are target genes of AGL16. • Taken together, our results show that AGL16 acts as a negative regulator transcriptionally suppressing key components in the stress response and may play a role in balancing stress response with growth.